Optimal nitrate supplementation in Phaeodactylum tricornutum culture medium increases biomass and fucoxanthin production - Afonso, Clélia (2022)
Phaeodactylum tricornutum is a model diatom with numerous potential applications in the industry, including the production of high-value carotenoid pigments such as fucoxanthin. This compound is a potent antioxidant currently extracted mainly from brown macroalgae. Fucoxanthin exhibits several biological properties with well-known beneficial effects in the treatment and prevention of lifestyle-related diseases. P. tricornutum offers a valuable alternative to macroalgae for fucoxanthin production as it has a specific productivity that is 10-fold higher as compared with macroalgae. However, production processes still need to be optimised to become a cost-effective alternative. In this work, we investigated the optimal supplementation of nitrate in a cultivation medium that is currently used for P. tricornutum and how this nitrate concentration affects cell growth and fucoxanthin production. It has previously been shown that the addition of sodium nitrate increases productivity, but optimal conditions were not accurately determined. In this report, we observed that the continuous increase in nitrate concentration did not lead to an increase in biomass and fucoxanthin content, but there was rather a window of optimal values of nitrate that led to maximum growth and pigment production. These results are discussed considering both the scale up for industrial production and the profitability of the process, as well as the implications in the cell's metabolism and effects in fucoxanthin production.